Diversity training for medical students: evaluating impact. Issue 1 (2nd January 2020) - Miah, Julia; Haque, Enam; Thampy, Harish
ABSTRACT: Diversity training is an important component of medical training in helping prepare learners to manage an increasingly diverse patient population. This work (conducted as part of a medical student project) evaluated Year 3 medical student views and perceived learning following participation in a one-day diversity-focussed teaching day at a UK medical school. Post-session evaluation data was analysed alongside data obtained from a focus group of student participants. Students largely valued specific teaching on this area of professional development and appreciated the safe learning environment in which they could freely share their beliefs and values in relation to potential sensitive issues. There was however suggestions made that longitudinal curricular integration would be a preferable and this delivery model has now been adopted at this institution.